Changing facets of leadership in East Asia: globalization, innovation and performance in Japan, South Korea and China. Issue 2 (15th March 2019) - Rowley, Chris; Ishikawa, Jun; Oh, Ingyu
ABSTRACT: Japan, South Korea and China are the three juggernauts of the East Asian economy. In gross domestic product terms, China is the world's second largest economy, Japan the third and South Korea the eleventh. Also, Japan and South Korea are the only two of the OECD's prestigious Development Assistance Committee members from Asia, providing a large combined annual budget to developing countries, and the only two Asian countries of the seven-member 50–20 Club with members with a population of 50 million or more and a per capita GDP of US$20, 000 or more. Many studies have offered explanations of this Asian economic and corporate success, although few have attempted to explain the leadership styles in these three countries. Globalization has also changed these economies enormously, leading to the possible convergence with universalism forces and commensurate globalization of their leadership styles. This collection, therefore, presents some of the most recent findings of leadership studies on Japan, South Korea and China in light of this.